The Diagnostic Utility of Brain Natriuretic Peptide in Heart Failure Patients Presenting with Acute Dyspnea: A Systematic Review and Meta-analysis - Mohammad Amin Karimi; Zahra Kazemi Ferezghi; Reza Khademi; Seyed Amirhossein Mazhari; Fatemeh Chichagi; Asma Rasouli; Reyhaneh Alikhani; Anis Sani; Shima Akhavan Rezayat; Nima Shakouri; Seyed Iraj Azimi; Faezeh Jadidian; et al. (Acta Medica Indonesiana)
Background: Patients with heart failure are often diagnosed based on clinical signs and serological markers. Finding biomarkers with greater sensitivity and specificity for heart failure patients who also have episodic dyspnea is a challenge for researchers. Thus, we conducted a systematic review and meta-analysis of previous research to determine the diagnostic value of B-type natriuretic peptide as a potential biomarker in heart failure patients experiencing acute dyspnea. Methods: By searching PubMed/Medline, Scopus, and Google Scholar up to March 2023, all cross-sectional and cohort studies were selected according to the PRISMA guidelines and assessed by the Deeks’ funnel plot asymmetry test for bias. Results: A total of thirty-five qualifying studies had their data extracted. In 26 investigations (n=16002), the precision of B-type natriuretic peptide was evaluated. There were significant differences in the reported sensitivity and specificity between trials. One research study yielded the lowest sensitivity of 0.76 (0.68, 0.82), with a prevalence of 46% for heart failure and a BNP level of ≥500 pg/ml. Specificity grew but stayed variable as the threshold rose, whereas sensitivity declined. A diagnostic meta-analysis was carried out on 14 trials (n=6313) to determine the accuracy of N-terminal probrain natriuretic peptide. When the threshold is raised, the pattern in NTproBNP is similar to that of B-type natriuretic peptides, with sensitivity falling and specificity increasing. Following the final analysis, the confidence areas surrounding the pooled sensitivity and specificity for BNP vs NTproBNP showed a distinct overlap. The overlap indicated that there was no statistically significant difference between the tests at the <100 pg/ml and ≤300 pg/ml rule-out levels, respectively (P>0.05). Conclusion: The meta-analysis reveals a substantial degree of congruity in the sensitivity and specificity between the levels of BNP and NTproBNP as biomarkers. Nevertheless, it's worth noting that, in the end, there exists a potential for overlooking heart failure diagnoses. Larger future studies, overcoming past limitations, could likely establish a consensus.